Development of Science E-Modules Based on Ethnoscience Work, Energy, and Simple Machine Junior High School - Yohana, Veby; Fakhruddin Z, Fakhruddin Z; Nasir , Muhammad (Journal of Educational Sciences, 2025)
The goal of this development is to produce teaching materials that are valid, practical, and feasible, while also integrating science concepts with the local wisdom of the Riau community to enhance students’ understanding and engagement in learning. The development process follows the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. During the Analysis stage, the focus is on identifying students’ needs, as well as analyzing the curriculum and learning materials. The Design stage involves developing the e-module’s format and content based on the ethnoscience framework. In the Development stage, an initial product is created and validated by expert lecturers, followed by one-on-one trials with three grade VIII students of SMP Negeri 4 Tambang who represent different ability levels high, medium, and low. The Implementation stage includes practicality testing with science teachers and grade VIII students. The results indicate that the e-module achieved a validation score of 0.88 (very valid category), teacher response of 92.86 (very practical category), and student response of 90.74 (very practical category). Therefore, the e-module is considered valid, practical, and suitable for use in science learning.